Strategies for cost reduction in DHL global forwarding's air freight operations in Bangladesh: a financial perspective - Haque, Mashrif (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023